How Preschoolers Use Cues of Dominance to Make Sense of Their Social Environment - Cheraffedine, Rawan; Mercier, Hugo; Clément, Fabrice; Kaufmann, Laurence; Berchtold, André; Reboul, Anne; Van der Henst, Jean-Baptiste (My University, 2015)
A series of four experiments investigated preschoolers’ abilities to make sense of dominance relations. Experiments 1 and 2 showed that as early as 3 years old, preschoolers are able to infer dominance not only from physical supremacy but also from decision power, age, and resources. Experiments 3 and 4 showed that preschoolers have expectations regarding the ways in which a dominant and a subordinate individual are likely to differ. In particular, they expect that an individual who imposes his choice on another will exhibit higher competence in games and will have more resources.